Mitochondrial Superoxide Production Negatively Regulates Neural Progenitor Proliferation and Cerebral Cortical Development123. (22nd October 2012) - Hou, Yan; Ouyang, Xin; Wan, Ruiqian; Cheng, Heping; Mattson, Mark P.; Cheng, Aiwu
Abstract: Although high amounts of reactive oxygen species (ROS) can damage cells, ROS can also play roles as second messengers, regulating diverse cellular processes. Here, we report that embryonic mouse cerebral cortical neural progenitor cells (NPCs) exhibit intermittent spontaneous bursts of mitochondrial superoxide (SO) generation (mitochondrial SO flashes) that require transient opening of membrane permeability transition pores (mPTP). This quantal SO production negatively regulates NPC self‐renewal. Mitochondrial SO scavengers and mPTP inhibitors reduce SO flash frequency and enhance NPC proliferation, whereas prolonged mPTP opening and SO generation increase SO flash incidence and decrease NPC proliferation. The inhibition of NPC proliferation by mitochondrial SO involves suppression of extracellular signal‐regulated kinases. Moreover, mice lacking SOD2 (SOD2−/− mice) exhibit significantly fewer proliferative NPCs and differentiated neurons in the embryonic cerebral cortex at midgestation compared with wild‐type littermates. Cultured SOD2−/− NPCs exhibit a significant increase in SO flash frequency and reduced NPC proliferation. Taken together, our findings suggest that mitochondrial SO flashes negatively regulate NPC self‐renewal in the developing cerebral cortex. STEM CELLS 2012;30:2535–2547